2022
DOI: 10.3390/ma15196927
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Fracture Resistance Testing of Polyether Ether Ketone (PEEK) Implant Abutments in an Ex Vivo Chewing Simulator Model

Abstract: Polyether ether ketone (PEEK) has been introduced into implant dentistry as a viable alternative to current implant abutment materials. However, data on its physico-mechanical properties are still scarce. The present study sought to shed light on this topic utilizing an ex vivo chewing simulator model. A total of 48 titanium two-piece implants were allocated into three groups (n = 16 per group): (1) implants with PEEK abutments and an internal butt-joint connection (PBJ), (2) implants with PEEK abutments and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…PEEK abutments have been introduced into implant dentistry as a viable alternative to current implant abutment materials [ 39 ]. Studies have indicated, firstly, that PEEK abutments should be used as a temporary abutment material [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEEK abutments have been introduced into implant dentistry as a viable alternative to current implant abutment materials [ 39 ]. Studies have indicated, firstly, that PEEK abutments should be used as a temporary abutment material [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated, firstly, that PEEK abutments should be used as a temporary abutment material [ 40 , 41 ]. Saravi in 2022 concluded that the application of PEEK can be used as a novel definitive implant abutment material, as PEEK abutments showed superior load-bearing properties compared to zirconia, although it was associated with greater microgaps at the implant–abutment complex [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Ortega-Martínez et al, PEEK abutments may be used as a metal-free alternative to Titanium abutments for long-term interim restorations [99]. Based on the findings of Saravi et al, they can also be used as an alternative to Zirconia abutments [100]. PEEK implants induce less stress shielding than Titanium [101].…”
Section: Peekmentioning
confidence: 99%
“…It was found that a maximum removal efficiency of about 99% was obtained. Saravi et al [13] studied the fatigue behavior of PEEK implant abutments. It was found that the PEEK implant abutments seem to be feasible, compared to zirconia implant abutments.…”
Section: Introductionmentioning
confidence: 99%